ChemInform Abstract: [4 + 2] vs [3 + 2] Annulations in the Nickel‐ and Cobalt‐Catalyzed Reaction of ortho‐Haloimines with Alkynes: Differential Reactivity Towards the Synthesis of Isoquinolines and Aminoindenes. Issue 21 (27th May 2014) - Mannathan, Subramaniyan; Cheng, Chien‐Hong
Abstract Review: [17 refs.